The contribution of small and medium diameter trees to biomass and carbon pools in Yabo, Sokoto State, Nigeria - Murtala Dangulla; Latifah Abd Manaf; Mansur Muhammad Aliero (Academia Environmental Sciences and Sustainability)
Increases in human population and human activities have led to corresponding increases in the amount of atmospheric carbon dioxide. The present rates, by far, supersede historical records, and by 2050, the global concentration is expected to reach 470 ppm even if the average concentration is controlled at 2 ppm per annum. Trees and vegetation, in general, perform the ecosystem service of storing and sequestering atmospheric carbon. However, it is widely believed that larger-diameter trees store more biomass and carbon stocks. This study assessed the contribution of small- and medium-diameter trees to regional carbon pools of the West African Savanna, using a general allometric equation. A total of 671 woody stems of ≥2 m height and ≥5 cm diameter, belonging to 40 species, 35 genera, and 19 families, were identified. The trees stored 120.2 kg of carbon stock, which translated to approximately 0.18 kg/tree. Although most of the trees enumerated in the study have small to medium diameters, few large-diameter trees including Combretum ghasalense (1.23 kg/tree), Ceiba pentandra (1.08 kg/tree), Faidherbia albida (0.92 kg/tree), and Prosopis africana (0.73 kg/tree) contributed the highest mean carbon stock in the area. The study confirms that larger-diameter trees account for much of biomass and carbon in a given area, but this does not underscore the contribution of smaller trees to the regional carbon stock especially in dry environments where they form a greater percentage of available trees. The study recommends the conservation of small- and medium-diameter trees to ensure the sustainability of this relatively dry environment.